Awareness Among Dairy Farmers Regarding Breeding and Health Practices in Una and Hoshiarpur - Singh, Ravdeep; Kumar Sharma, Rakesh; Singh, Jaswinder; Kasrija, Rajesh; Deshmukh, Bharti; Hon parkhe, Mrigank (The Indian Journal of Animal Reproduction, 2025)
This study was conducted to assess and compare the awareness and adoption of reproductive and healthcare manage ment practices among dairy farmers in Hoshiarpur district of Punjab and Una district of Himachal Pradesh. A total of  80 respondents (40 from each district) were selected using a purposive random sampling method. Data were collected  through a pre-tested structured interview schedule and analysed using descriptive statistics and t-tests to determine the  significance of observed differences.The results revealed significant regional disparities in both awareness and adoption  of recommended dairy practices. Farmers from Hoshiarpur consistently reported higher mean scores across most indi cators. In reproductive and breeding management, significant differences (p < 0.05) were observed in farmers’ knowledge  regarding the importance of age at first insemination (Hoshiarpur: M = 0.90 ± 0.04; Una: M = 0.70 ± 0.07), preference for  artificial insemination over natural service (0.82 ± 0.06 vs. 0.62 ± 0.07), awareness of heat detection (0.82 ± 0.06 vs. 0.60  ± 0.07), semen quality (0.75 ± 0.06 vs. 0.52 ± 0.07) and use of veterinary help during parturition (0.82 ± 0.06 vs. 0.57 ±  0.07). In terms of healthcare practices, significant differences were found in seasonal vaccination awareness (0.95 ± 0.03  vs. 0.80 ± 0.06) and application of prophylactic measures against contagious diseases (0.32 ± 0.07 vs. 0.12 ± 0.05).The  overall mean adoption score was significantly higher in Hoshiarpur (0.68 ± 0.05) than Una (0.53 ± 0.06), indicating more  effective extension and veterinary service delivery in Punjab. These findings emphasize the need for focused awareness  programs, improved service infrastructure and targeted interventions in Una district to enhance reproductive efficiency  and health management in dairy farming.
Keywords: Awareness; Dairy farming; Healthcare management; Himachal Pradesh; Punjab; Reproductive management